2007
DOI: 10.1007/s10886-006-9239-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature as a Modifier of Plant–Herbivore Interaction

Abstract: Temperature directly affects the growth, survival, and development rates of poikilothermic insect herbivores; it may also have an important indirect impact, via the activities of plant defensive enzymes. The effects of wounding birch leaves and temperature on the growth and development rates of a Lepidopteran moth, Epirrita autumnata, were studied. We also examined the activities of a mountain birch (Betula pubescesns spp. czerepanovii) defensive enzymes, specifically the polyphenoloxidases (PPOs), in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Although in earlier studies we demonstrated that PPOs are rapidly induced by herbivory on birch (Ruuhola and Yang 2006;Yang et al 2007), this is the Wrst study in which PPOs were shown to correlate negatively with the performance of autumnal moth larvae. Interestingly, in our earlier study, we found that temperature interacts with wounding: at 12°C herbivory decreased PPO activity whereas at 24°C, herbivory induced the activity ); thus temperature may have an important role in the defence of birches against moth larvae.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Although in earlier studies we demonstrated that PPOs are rapidly induced by herbivory on birch (Ruuhola and Yang 2006;Yang et al 2007), this is the Wrst study in which PPOs were shown to correlate negatively with the performance of autumnal moth larvae. Interestingly, in our earlier study, we found that temperature interacts with wounding: at 12°C herbivory decreased PPO activity whereas at 24°C, herbivory induced the activity ); thus temperature may have an important role in the defence of birches against moth larvae.…”
Section: Discussionmentioning
confidence: 50%
“…poplar (Constabel et al 2000;Haruta et al 2001) and aspen (Tscharntke et al 2001), oxidases play an important role in defence against multiple herbivores, although their role in the defence of other tree species has largely been ignored. In our earlier studies, we demonstrated that both birch PODs (Ruuhola and Yang 2006) and PPOs (Ruuhola and Yang 2006;Yang et al 2007) are induced by herbivory.…”
Section: Introductionmentioning
confidence: 85%
“…Herbivory but not UV-B exposure increased the activities of birch PPOs and the effect of herbivory on the birch phenolics was stronger than the effect of UV-B. In earlier studies with mountain birch, PPO activities were induced by herbivore wounding (Ruuhola and Yang 2006;Yang et al 2007a;Ruuhola et al 2008). However, due to the use of clonal material, the differences between control plants and herbivore-treated plants were clearer and more marked in the current study: the greatest difference being a ca.…”
Section: Discussionmentioning
confidence: 87%
“…In spite of numerous studies, researchers have not been able to link the performance of the autumnal moth (Epirrita autumnata Borkhausen) to the content of a certain phenolic compound and the results of different studies have been variable (Haukioja 2003). One explanation could be that some phenolics may require enzymes to activate their defensive properties (Ruuhola et al 2008) such as peroxidases (PODs) or polyphenol oxidases (PPOs) that are both induced by herbivore attacks and wounding (Felton et al 1989;Tscharntke et al 2001;Ruuhola and Yang 2006;Yang et al 2007a;Ruuhola et al 2008). PODs and PPOs catalyse the conversion of plant diphenols to reactive quinones, which bind to amino acids and proteins, decreasing the nutritive value of plants (Felton et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Thus enzyme activities alone probably do not dictate the impact of oxidation on herbivores; rather, enzymatic activities interact with the level of available substrates, possibly also with the level of target molecules, in determining resistance against folivores (see Bi et al 1997). Spatial and temporal variation in the activities of foliar enzymes, together with the rapid inducibility of enzymes by herbivory (see Ruuhola & Yang 2006;Yang et al in press), make birches a very unpredictable source of food; together with the high variability in the contents of primary and secondary compounds, this may lead to patchy feeding. Kaitaniemi et al (2004) showed that tree architecture interacts with defoliation treatment in determining tree suitability for autumnal moth larvae.…”
Section: Implications For Ecological Interactionsmentioning
confidence: 99%